Mirage and Reality Interplay in Tom Tykwer’s A Hologram for a King - Sutandio, Anton (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p39, 2018)
This article discusses 2016 film A Hologram for a King, directed by Tom Tykwer in the context of the interplay between mirage and reality.  Set in Saudi Arabia, this film revolves around the story of an American consultant, Alan Clay, who attempts to sell a hollographic teleconferencing system to the king.  The film is imbued with captivating and symbolic visuals that point to the interplay between mirage and reality.  This article will focus on how the cinematography and mise-en-scene of the film help supporting the interplay between mirage and reality, and to show what the film comments on the interplay in regard to our contemporary world.  The method used is a film scene analysis by focusing on the important scenes in the film.   The findings show that the director cleverly utilizes cinematic techniques to emphasize the main theme of the film and to offer his own viewpoint on the interplay between mirage and reality.